PENDUGAAN CADANGAN KARBON VEGETASI DI SEMPADAN SUNGAI PADA KAWASAN HUTAN DENGAN TUJUAN KHUSUS (KHDTK) UNIVERSITAS LAMBUNG MANGKURAT - Gadis Yuniar Paradika; Kissinger Kissinger; Arfa Agustina Rezekiah (Jurnal Sylva Scienteae, 2021)
River borders as wetlands has the possibility that the surrounding vegetation can absorb and store more carbon. The purpose of research is to analyze the composition of vegetation types in the river borders, suspect and analyze the carbon reserves stored on the boundary of the river and estimate amount of carbon dioxide that is able to be absorbed by vegetation on the river borders KHDTK Lambung Mangkurat University. The method of the plot selection is purposive sampling on the left and right of the river as many as 24 plots. Data collection uses the analysis of vegetation in a non-destructive way on any growth of vegetation. Sampling for the calculation of biomass and carbon content of trees, underplants, litter and necromassa by means of destructive. The Total type that makes up the standing structure found at all levels of vegetation is 80 species. 41 species are found at the seedling types, 58 species of sapling types, 41 species of pole tpes and 39 tree level type. Total carbon reserves are stored in research locations of 61 tonnes/ha of all growth tree types, necromassa, underplants and litter. Meanwhile, the total carbon dioxide that is able to be absorbed by the vegetation at the research site is 203.72 tons/ha of all levels of tree growth, necromassa, Underplant and litter. The results of research is show the vegetation of river borders has the potential as an absorbent and stores a large carbon.Keywords: Carbon reserves; Vegetation; River borders